Glass Cloth

By optimizing gap and fiber configurations in glass cloths, the issues of vertical wrinkles and pinholes in prepregs are addressed, ensuring high-quality prepreg production.

JP7626402B2Active Publication Date: 2025-02-04UNITIKA LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021554916
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-29
Publication Date
2025-02-04
Estimated Expiration
2040-10-29

AI Technical Summary

Technical Problem

Low-quality glass cloths used in prepregs for printed wiring boards are prone to vertical wrinkles and pinhole formation due to their low mass ratio and structural properties, which are exacerbated by the impregnation with resin solutions.

Method used

The glass cloth is designed with specific gap and fiber configurations, including gap design values between adjacent weft and warp fibers of 95 μm or less, a ratio of gap measurements (IW/IF) of 1.23 or 1.45 or less, and a basket hole area ratio between 12.0% and 20.0%, to control vertical wrinkle and pinhole occurrence.

Benefits of technology

The solution effectively reduces pinhole and vertical wrinkle formation in prepregs, maintaining high product quality and reliability by balancing structural integrity and resin impregnation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626402000001
    Figure 0007626402000001
  • Figure 0007626402000002
    Figure 0007626402000002
  • Figure 0007626402000003
    Figure 0007626402000003
Patent Text Reader

Abstract

The present invention addresses the problem of providing a low-mass glass cloth that, even when impregnated with a resin solution to produce a prepreg that contains, by mass, a low proportion of the glass cloth, can particularly effectively suppress the occurrence of pinholes and longitudinal wrinkles. A glass cloth that has a mass of no more than 10.0 g / m2. The design value Iwd for the gaps between adjacent warp threads is no more than 95 μm, and the design value Ifd for the gaps between adjacent weft threads is no more than 95 μm. The ratio (Iw / If) of the actual value (Iw) of the gaps between adjacent warp threads and the actual value (If) of the gaps between adjacent weft threads is 1.23–1.45. The basket hole area fraction is 12.0%–20.0%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass cloth. [Background technology]

[0002] In recent years, with the miniaturization of electronic devices, printed wiring boards are required to be lightweight, and materials used are also required to have low mass. Prepregs in which glass cloth is impregnated with resin are used to manufacture printed wiring boards, but with the weight reduction of the above electronic devices, the prepregs are also required to have low mass. Similarly, the glass cloth contained in the prepregs is also required to have low mass.

[0003] As a low-mass glass cloth, for example, a glass cloth satisfying the following (i) to (iv) is known (see, for example, Patent Document 1). (i) The degree of opening shown in the following formula (1) is 70 to 90% for the warp yarn and 95 to 120% for the weft yarn. Openness (%) = {(25 x 1000) / WD-I} / (D x N) x 100 (1) WD: Warp or weft density (threads / 25mm) I: Gap between adjacent warp or weft threads (μm) D: average filament diameter of warp or weft (μm) N: Average number of filaments in the warp or weft (ii) Either the gap distance between adjacent warp yarns or the gap distance between adjacent weft yarns is 100 μm or less. (iii) The thickness, measured in accordance with JIS R 3420:2013 7.10.1, is 14 μm or less. (iv) The cloth mass measured in accordance with JIS R 3420:2103 7.2 is 11 g / m 2 below.

[0004] According to the glass cloth in Patent Document 1, when the thickness is reduced to 14 μm or less and a thin prepreg having a thickness of, for example, 20 μm or less is formed into a substrate using the prepreg, the occurrence of pinholes can be suppressed.

[0005] In addition, a low-mass glass cloth is made of warp and weft yarns each formed by bundling 14 to 55 glass filaments having a diameter in the range of 3.0 to 4.2 μm, the weaving density of the warp and weft yarns being in the range of 86 to 140 yarns / 25 mm, the thickness being in the range of 7.5 to 12.0 μm, and the length per m 2 a mass in the range of 6.0 to 10.0 g per unit area, and an average number of steps, expressed as a value obtained by dividing the thickness of the glass cloth by the average value of the diameter of the glass filaments of the warp and the diameter of the glass filaments of the weft (thickness of the glass cloth / {(diameter of the glass filaments of the warp+diameter of the glass filaments of the weft) / 2}), is in the range of 2.00 or more and less than 3.00, There is known a glass cloth having an average degree of opening, expressed as the geometric mean ((warp opening degree x weft opening degree) / 2) of the opening degree of the weft (weft width / (diameter of glass filaments constituting the weft x number of glass filaments constituting the weft)), in the range of 1.000 to 1.300, and a width ratio, expressed as the ratio of the warp width to the weft width (warp width / weft width), in the range of 0.720 to 0.960 (see, for example, Patent Document 2).

[0006] According to the glass cloth of Patent Document 2, even if the average number of rows is less than 3.00, it is possible to suppress the occurrence of pinholes in a prepreg using the glass cloth, and it is also possible to maintain excellent appearance quality of the prepreg due to the reduced fuzzing of the glass cloth. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-43873 A [Patent Document 2] JP 2018-21274 A Summary of the Invention [Problem to be solved by the invention]

[0008] From the viewpoint of insulation reliability, low-mass prepregs are often used with a low mass ratio of glass cloth, for example, a ratio of the mass of glass cloth to the total mass of the prepreg being about 10 to 40 mass%. However, the present inventors have found through their studies that when the glass cloths of Patent Documents 1 and 2 described above have a low mass ratio of glass cloth when made into prepregs and are impregnated with a resin solution and cured, the resulting prepregs may have wrinkles (vertical wrinkles) running in the machine direction during production.

[0009] Therefore, the present invention has an object to solve the above problems and to provide a glass cloth that can remarkably effectively suppress the occurrence of pinholes and the above-mentioned vertical wrinkles, even when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to prepare a prepreg. [Means for solving the problem]

[0010] The inventors of the present invention have studied the cause of the above problem, and have found that when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low and cured, the tension in the weft direction (glass cloth width direction) of the glass cloth is significantly lower than the tension in the warp direction (glass cloth length direction) of the glass cloth. In addition, in the glass cloth of Patent Document 1, the weft tends to move slightly in the glass cloth width direction due to the curing shrinkage when the resin impregnated in the glass cloth is cured, and as a result, the above-mentioned vertical wrinkles are likely to occur. Specifically, in the glass cloth of Patent Document 1, the following factors (i) to (iii) and the like work together, and it is thought that this causes the weft to move slightly in the glass cloth width direction, and thus vertical wrinkles are likely to occur. (i) The spacing between the gaps between adjacent warp threads is larger than the spacing between the gaps between adjacent weft threads, so that the warp threads do not adequately grip the weft threads. (ii) The glass cloth is originally thin, and the warp and weft threads are thin and flexible. (iii) When a low-mass glass cloth is impregnated with a resin solution and cured so that the mass ratio of the glass cloth is low, the weft yarns are more likely to move in the width direction of the glass cloth due to curing shrinkage, compared to when the glass cloth is impregnated with a resin solution and cured so that the mass ratio of the glass cloth is relatively high.

[0011] The inventors also considered that the glass cloth of Patent Document 2 was subjected to an excessive fiber opening process, and in particular, each filament constituting the weft yarn was bent, which caused vertical wrinkles to easily occur. That is, when each filament constituting the weft yarn is bent, each filament is present in the glass cloth in a loose state. The loose filaments are in a state where they are likely to move in the width direction of the glass cloth, and if a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low and cured, the weft yarn will move slightly in the width direction of the glass cloth due to the loose filaments during curing and shrinkage, and vertical wrinkles will easily occur as a result.

[0012] On the other hand, in consideration of the above-mentioned mechanism of action, it was thought that the suppression of pinhole generation and the suppression of vertical wrinkle generation could be achieved by increasing the warp and weft densities of the glass cloth or by increasing the number of filaments in the warp and weft. However, the present inventors found that there was a problem in that increasing the warp and weft densities of the glass cloth or increasing the number of filaments in the warp and weft would increase the mass of the glass cloth and therefore the mass of the prepreg. They also found that if the mass ratio of the glass cloth in the prepreg is too high, the glass cloth will be exposed from the surface of the prepreg, and the exposed glass cloth will come into direct contact with the signal layer, thereby impairing the insulation reliability.

[0013] Furthermore, the present inventors have found that as the glass cloth becomes thinner, if the warp and weft densities of the glass cloth are increased, the number of filaments in the warp and weft threads is increased, or excessive fiber-opening treatment is performed, the gap space surrounded by adjacent warp and weft threads becomes extremely small, which causes a problem that internal distortion is likely to occur in the glass cloth and vertical wrinkles are likely to occur.

[0014] The present inventors have conducted intensive studies to solve the above problems, and have found that when a low-mass glass cloth is impregnated with a resin solution to obtain a low mass glass cloth and a prepreg, the occurrence of pinholes and the above-mentioned vertical wrinkles can be remarkably effectively suppressed by satisfying the following: (1) in the glass cloth, the design value Iwd of the gap between adjacent warps and the design value Ifd of the gap between adjacent wefts are set to 95 μm or less, (2) in order to sufficiently hold the warp and weft threads while keeping the mass of the glass cloth to a specific mass or less, the ratio (Iw / If) of the actual measured value of the gap (Iw) between adjacent warps and the actual measured value of the gap (If) between adjacent weft threads is set to 1.23 to 1.45, and (3) the area ratio of basket holes (openings) formed by adjacent warps and adjacent weft threads is set to 12.0% to 20.0%. The present invention has been completed based on these findings and through further studies.

[0015] That is, the present invention provides the following aspects. Item 1. Mass is 10.0g / m 2 The following glass cloth: The gap design value Iwd between adjacent warp yarns shown in the following formula (1) is 95 μm or less, and the gap design value Ifd between adjacent weft yarns shown in the following formula (2) is 95 μm or less, The ratio (Iw / If) of the measured gap between adjacent warp yarns (Iw) to the measured gap between adjacent weft yarns (If) is 1.23 or more and 1.45 or less, and A glass cloth having a basket hole area ratio, as shown in the following formula (3), of 12.0% or more and 20.0% or less.

number

number

[0016] According to the glass cloth of the present invention, the mass is 10.0 g / m 2The following glass cloth has a designed gap Iwd between adjacent warp yarns of 95 μm or less, a designed gap Ifd between adjacent weft yarns of 95 μm, a ratio (Iw / If) of the measured gap Iw between adjacent warp yarns and the measured gap If between adjacent weft yarns of 1.23 or more and 1.45 or less, and a basket hole area ratio of 12.0% or more and 20.0% or less. Therefore, when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, it becomes possible to remarkably effectively suppress the occurrence of pinholes and the above-mentioned vertical wrinkles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] 1. Glass cloth Mass is 10g / m 2 The following glass cloth is characterized in that the design gap value Iwd between adjacent warp yarns shown in formula (1) is 95 μm or less, and the design gap value Ifd between adjacent weft yarns shown in formula (2) is 95 μm or less, the ratio (Iw / If) of the actual gap value (Iw) between adjacent warp yarns to the actual gap value (If) between adjacent weft yarns is 1.23 to 1.45, and the basket hole area ratio shown in formula (3) is 12.0% to 20.0%. The glass cloth of the present invention will be described in detail below.

[0018] The glass cloth of the present invention has a mass of 10.0 g / m 2 It is fine if it is less than 9.5g / m 2 The lower limit of the above range of mass is not particularly limited, but is preferably 5.0 g / m or less. 2 More than 6.0g / m 2 More than 7.0 g / m is preferable. 2 More preferably, 8.0 g / m or more 2 More preferably, 8.5 g / m 2 More preferably, the mass of the glass cloth of the present invention is 5.0 g / m 2 More than 10g / m 2 Less than 6.0 g / m 2 More than 10g / m 2 Less than 7.0 g / m2 More than 9.5g / m 2 Less than 8.5 g / m, more preferably 8.5 g / m 2 More than 9.5g / m 2 In the present invention, the above mass is a value measured and calculated in accordance with the provisions of "7.2 Mass (mass) of cloth and mat" in the Japanese Industrial Standard JIS R 3420 2013 (general test method for glass fibers).

[0019] In the glass cloth of the present invention, the design value Iwd of the gap between adjacent warps as shown in the following formula (1) is 95 μm or less, and the design value Ifd of the gap between adjacent wefts as shown in the following formula (2) is 95 μm or less. The lower limit values ​​of the design value Iwd of the gap between the warps and the design value Ifd of the gap between the wefts are not particularly limited, but from the viewpoint of further easily achieving both suppression of pinhole generation and suppression of vertical wrinkle generation, they are preferably 60 μm or more, more preferably 70 μm or more, and even more preferably 75 μm or more. The design value Iwd of the gap between the warps in the glass cloth of the present invention is specifically 60 μm or more and 95 μm or less, preferably 70 μm or more and 95 μm or less, and more preferably 75 μm or more and 95 μm or less. The design value Ifd of the gap between the wefts in the glass cloth of the present invention is specifically 60 μm or more and 95 μm or less, preferably 70 μm or more and 95 μm or less, and more preferably 75 μm or more and 95 μm or less. In particular, by having both the designed gap value Iwd and the designed gap value Ifd be 75 μm or more, it becomes easier to preferably obtain the range of the ratio (Iw / If) of the actual measured gap value (Iw) between adjacent warp yarns and the actual measured gap value (If) between adjacent weft yarns, and the range of the basket hole area ratio, which will be described later.

number

[0020] The above-mentioned warp gap design value Iwd and weft gap design value Ifd are first assumed to be arranged in a line without gaps in the glass yarn width direction in the warp and weft (glass yarn) consisting of a plurality of filaments. In this assumption, the width (μm) of the virtual glass yarn can be calculated by the average filament diameter x the average number of filaments (i.e., Dw x Nw for warp yarns, Df x Nf for weft yarns). Next, since the weaving density (Ww for warp yarns, Wf for weft yarns) is the number of glass yarns per 25 mm (25000 μm) as described later, the sum of the width of the glass yarn and the gap between adjacent glass yarns can be calculated by dividing 25000 μm by the weaving density (25000 / Ww for warp yarns, 25000 / Wf for weft yarns). Then, by subtracting the virtual glass thread width from the sum of the width of the glass thread and the width of adjacent glass threads, the virtual gap spacing between adjacent warp threads and the virtual gap spacing between adjacent weft threads can be calculated, and these are set as the gap design value Iwd between adjacent warp threads and the gap design value Ifd between adjacent weft threads, respectively.

[0021] The glass cloth given as a specific example in Patent Document 2 is designed so that the above-mentioned warp gap design value Iwd and weft gap design value Ifd exceed 100 μm, and is manufactured by a method of reducing the gaps by excessive fiber opening. Therefore, the present inventor considered that the glass cloth in the example of Patent Document 2 has each filament present in the glass cloth in a loose state, which causes each filament constituting the weft, in particular, to bend, and as a result, vertical wrinkles are likely to occur. The present inventor then found that the occurrence of pinholes and the above-mentioned vertical wrinkles can be remarkably effectively suppressed by setting the warp gap design value Iwd and the weft gap design value Ifd within the above-mentioned specific ranges.

[0022] In the glass cloth of the present invention, the warp density Ww and weft density Wf (pieces / 25 mm) of the glass cloth are not particularly limited, but from the viewpoint of more easily achieving both suppression of pinhole generation and suppression of vertical wrinkle generation when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, the warp density Ww and weft density Wf are preferably 90 pieces / 25 mm or more and 160 pieces / 25 mm or less, more preferably 95 pieces / 25 mm or more and 150 pieces / 25 mm or less, and even more preferably 100 pieces / 25 mm or more and 125 pieces / 25 mm or less. In the present invention, the warp density and weft density are values ​​measured and calculated according to the provisions of "7.9 Density (weaving density)" of the Japanese Industrial Standard JIS R 3420 2013 (General test method for glass fibers).

[0023] In the glass cloth of the present invention, the average filament diameter Dw of the filaments constituting the warp yarns (glass yarns) and the average filament diameter Df of the filaments constituting the weft yarns (glass yarns) are not particularly limited, but from the viewpoint of making it easier to achieve both the suppression of pinhole generation and the suppression of vertical wrinkles when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, the average filament diameter Dw is preferably 2.5 μm or more and 4.0 μm or less, and more preferably 3.0 μm or more and 3.7 μm or less.

[0024] In the glass cloth of the present invention, the average number Nw of filaments constituting the warp yarns (glass yarns) and the average number Nf of filaments constituting the weft yarns (glass yarns) constituting the glass cloth are, from the viewpoint of making it easier to simultaneously suppress the occurrence of pinholes and the occurrence of vertical wrinkles when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, preferably 25 to 50, more preferably 30 to 40, and even more preferably 34 to 40.

[0025] In the present invention, the average filament diameters (Dw and Df) and the average numbers of filaments (Nw and Nf) are measured and calculated as follows.

[0026] That is, two pieces of glass cloth were cut into 30 cm squares, one for observing the warp threads and the other for observing the weft threads, and each was embedded in epoxy resin (product name 3091, manufactured by Marumoto Struers K.K.), hardened, and polished to the point where the warp and weft threads could be observed. Using a scanning electron microscope (SEM), the filament diameter was observed and measured at a magnification of 1000x, and the number of filaments was observed and measured at a magnification of 500x. (1) Average filament diameter of glass yarn (μm) Thirty warp and weft threads are randomly selected, and the diameters of all filaments (largest part) of the 30 glass threads are measured and the average value is calculated to obtain the average filament diameter of the warp and weft threads. (2) Average number of filaments (pieces) Twenty threads are randomly selected for each of the warp and weft yarns, and the total number of filaments in the 20 glass threads is measured and the average value is calculated to obtain the average filament diameter of the warp and weft yarns.

[0027] In the glass cloth of the present invention, the count (tex) of the warp and weft yarns is not particularly limited, but from the viewpoint of more easily achieving both suppression of pinhole generation and suppression of vertical wrinkle generation when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, the count is preferably 0.5 tex to 1.2 tex, more preferably 0.6 tex to 1.1 tex, and even more preferably 0.9 tex to 1.1 tex. In the present invention, the count of the warp and weft yarns is a value measured and calculated according to the specification of "7.1 Count" of the Japanese Industrial Standard JIS R 3420 2013 (General Test Method for Glass Fibers).

[0028] In the glass cloth of the present invention, the glass material constituting the warp and weft is not particularly limited, and known glass materials can be used. Specific examples of the glass material include alkali-free glass (E glass), acid-resistant alkali-containing glass (C glass), high-strength, high-elasticity glass (S glass, T glass, UT glass (manufactured by Unitika Glass Fiber Co., Ltd.), etc.), alkali-resistant glass (AR glass), low-dielectric glass (NE glass, L glass, LU glass (manufactured by Unitika Glass Fiber Co., Ltd.), etc.). Among these glass materials, alkali-free glass (E glass) is preferred, as it is highly versatile. The glass fibers constituting the glass cloth may be made of one type of glass material, or may be a combination of two or more types of glass fibers made of different glass materials.

[0029] In the glass cloth of the present invention, the ratio (Iw / If) of the measured gap (Iw) between adjacent warp yarns to the measured gap (If) between adjacent weft yarns is 1.23 or more and 1.45 or less. By making the ratio (Iw / If) 1.45 or less, the weft yarns are sufficiently gripped by the warp yarns, and when a low-mass glass cloth is impregnated with a resin solution and cured so that the mass ratio of the glass cloth is low, the weft yarns are suppressed from moving slightly in the glass cloth width direction, and the occurrence of vertical wrinkles due to this can be sufficiently prevented. In addition, by making the ratio 1.23 or more, the occurrence of pinholes can be sufficiently suppressed when a low-mass glass cloth is impregnated with a resin solution and cured so that the mass ratio of the glass cloth is low. When a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, from the viewpoint of making it easier to simultaneously suppress the occurrence of pinholes and the occurrence of vertical wrinkles, the ratio (Iw / If) is preferably 1.25 or more and 1.45 or less, more preferably 1.30 or more and 1.40 or less, and even more preferably 1.34 to 1.44.

[0030] In the present invention, the measured gap value Iw between adjacent warp yarns and the measured gap value If between adjacent weft yarns are measured and calculated as follows. That is, first, a glass cloth is cut from three arbitrarily selected locations to a size that allows 100 consecutive gaps to be observed for both warp and weft yarns, and these are used as samples. Next, the sample is observed and measured for the gap interval at a magnification of 150 times using a microscope. Specifically, 100 consecutive gaps on the same straight line in each of the warp and weft directions of the cloth are observed from the normal direction of the glass cloth plane. This is performed for the three arbitrarily selected locations, and the gap intervals are measured for a total of 300 locations for both warp and weft yarns, and the average value of the gap intervals at these 300 locations is used as the measured gap value.

[0031] In the glass cloth of the present invention, the measured gap Iw between adjacent warp yarns is not particularly limited as long as the above ratio (Iw / If) is satisfied, and may be, for example, 70 μm or more and 120 μm or less. From the viewpoint of further suppressing pinhole generation and suppressing vertical wrinkle generation when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, the measured gap Iw between adjacent warp yarns is more preferably 80 μm or more and 110 μm or less, and even more preferably 90 μm or more and 110 μm or less.

[0032] In the glass cloth of the present invention, the measured gap If between adjacent weft yarns is not particularly limited as long as the above ratio (Iw / If) is satisfied, and may be, for example, 60 μm or more and 100 μm or less. From the viewpoint of further suppressing the occurrence of pinholes and the occurrence of vertical wrinkles when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, the measured gap If between adjacent weft yarns is more preferably 60 μm or more and 80 μm or less, and even more preferably 62 μm or more and 80 μm or less.

[0033] In the glass cloth of the present invention, the ratio (Iw / Iwd) of the measured gap (Iw) between adjacent warp threads to the designed gap Iwd (μm) between adjacent warp threads is, for example, 1.00 or more and 1.30 or less. When a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, from the viewpoint of further suppressing both the occurrence of pinholes and the occurrence of vertical wrinkles, the ratio (Iw / Iwd) is preferably 1.10 or more and 1.18 or less.

[0034] In the glass cloth of the present invention, the ratio (If / Ifd) of the measured gap (If) between adjacent wefts to the designed gap Ifd (μm) between adjacent wefts is, for example, 0.70 or more and 1.00 or less. When a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to prepare a prepreg, from the viewpoint of further suppressing both the occurrence of pinholes and the occurrence of vertical wrinkles, the ratio (If / Ifd) is preferably 0.80 or more and 1.00 or less.

[0035] The glass cloth of the present invention has a basket hole area ratio of 12.0% or more and 20.0% or less, as shown in the following formula (3). By making the basket hole area ratio 12% or more, the glass cloth of the present invention is less likely to have internal distortion, and is less likely to have vertical wrinkles when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg. Furthermore, by making the basket hole area 20.0% or less, the glass cloth of the present invention is more likely to suppress the generation of pinholes when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg. From the viewpoint of further achieving both the suppression of pinhole generation and the suppression of vertical wrinkle generation when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, the basket hole area ratio is preferably 12.0% or more and 18.0% or less, and more preferably 12.0% or more and 17.0% or less.

number

[0036] In the glass cloth of the present invention, the basket hole area is not particularly limited as long as it satisfies the basket hole area ratio described above. However, when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to prepare a prepreg, from the viewpoint of further suppressing the occurrence of pinholes and the occurrence of vertical wrinkles, the basket hole area is preferably set to, for example, 3,000 to 12,000 μm. 2 5000 to 9000 μm 2 More preferably, 5500 to 8500 μm 2 The basket hole area is calculated by multiplying the above-mentioned measured gap value Iw (μm) between adjacent warp yarns by the above-mentioned measured gap value If (μm) between adjacent weft yarns.

[0037] In the glass cloth of the present invention, the design value of the basket hole area is not particularly limited. However, from the viewpoint of further suppressing the occurrence of pinholes and the occurrence of vertical wrinkles when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, the design value of the basket hole area is, for example, 3000 to 12000 μm 2 5000 to 9000 μm 2 More preferably, 5500 to 9000 μm 2 In the present invention, the designed basket hole area is a value calculated by multiplying the designed gap value Iwd (μm) between adjacent warps by the designed gap value Ifd (μm) between adjacent wefts.

[0038] In the glass cloth of the present invention, the ratio of the basket hole area to the above-mentioned designed basket hole area (basket hole area / designed basket hole area) is not particularly limited, but from the viewpoint of further achieving both suppression of pinhole generation and suppression of vertical wrinkles when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, the ratio is 0.8 to 1.2, and more preferably 0.9 to 1.1.

[0039] The thickness of the glass cloth of the present invention is not particularly limited, but may be, for example, 12 μm or less, and preferably 11 μm or less. The lower limit may be, for example, 6 μm or more, preferably 7 μm or more, and more preferably 8 μm or more. The thickness of the glass cloth of the present invention is specifically, for example, 6 μm or more and 12 μm or less, preferably 7 μm or more and 11 μm or less, and more preferably 8 μm or more and 11 μm or less.

[0040] The weave of the glass cloth is not particularly limited, and examples thereof include plain weave, satin weave, twill weave, basket weave, and rib weave. Among these, plain weave is preferable. The glass cloth of the present invention is preferably made into a glass cloth roll product. The length of the glass cloth roll product is, for example, 100 m or more, preferably 100 m or more and 3000 m or less.

[0041] The method for producing the glass cloth of the present invention is not particularly limited as long as a glass cloth satisfying the above-mentioned properties can be obtained, but a preferred example of the method for producing the glass cloth of the present invention will be described below.

[0042] In a preferred embodiment of the method for producing a glass cloth of the present invention, a glass cloth having a mass of 10 g / m 2The following is a method for producing a glass cloth, in which a fiber-opening process is performed so that a designed gap value Iwd between adjacent warp yarns shown in the following formula (1) is 95 μm or less, and a designed gap value Ifd between adjacent weft yarns shown in the following formula (2) is 95 μm or less, while a ratio (Iw / If) of an actual measured gap value (Iw) between adjacent warp yarns and an actual measured gap value (If) between adjacent weft yarns is 1.23 to 1.45, and a basket hole area ratio shown in the following formula (3) is 12% to 20%.

number

[0043] As described above, the weave density of the warp and weft yarns constituting the glass cloth, and the average diameter and number of the filaments constituting the warp and weft yarns are adjusted to set the designed gap between adjacent warp yarns and the designed gap between adjacent weft yarns, and a fiber-opening process is performed so that the ratio (Iw / If) of the measured gap between adjacent warp yarns (Iw) to the measured gap between adjacent weft yarns (If) is 1.23 to 1.45 and the basket hole area ratio is 12% to 20%, whereby when a low-mass glass cloth is impregnated with a resin solution so that the mass ratio of the glass cloth is low to form a prepreg, it is possible to suppress both the occurrence of pinholes and the occurrence of vertical wrinkles.

[0044] That is, a preferred example of the method for producing glass cloth of the present invention is a method for producing a glass cloth having a mass of 10 g / m 2 The method includes a step of performing a fiber-spreading process on a glass cloth having a designed gap value Iwd between adjacent warp yarns of 95 μm or less and a designed gap value Ifd between adjacent weft yarns of 95 μm or less, and the fiber-spreading process is performed so that the ratio (Iw / If) of the actual gap value (Iw) between adjacent warp yarns and the actual gap value (If) between adjacent weft yarns is 1.23 or more and 1.45 or less, and the basket hole area ratio is 12% or more and 20% or less.

[0045] Mass is 10g / m 2Hereinafter, a glass cloth having a designed gap value Iwd between adjacent warp yarns of 95 μm or less and a designed gap value Ifd between adjacent weft yarns of 95 μm or less can be obtained by adjusting the weaving density of the warp yarns and weft yarns used, and the average diameter and number of filaments constituting the warp yarns and weft yarns, and weaving the warp yarns and weft yarns. Any conventionally known method may be used as a method for weaving a glass cloth, and examples of such methods include a method in which the warp yarns are subjected to a warping process and a sizing process, and then the weft yarns are driven in using a jet loom (e.g., an air jet loom, a water jet loom, etc.), a Sulzer loom, a Rapier loom, etc.

[0046] The woven glass cloth is subjected to a fiber-opening process so that the ratio (Iw / If) is 1.23 or more and 1.45 or less, and the basket hole area ratio is 12% or more and 20% or less. Examples of the method for fiber-opening include water flow processing in which water flow pressure is applied; processing in which high-frequency vibration is applied using water (e.g., degassed water, ion-exchanged water, deionized water, electrolytic cation water, electrolytic anion water, etc.) as a medium; and pressure processing using rolls. In addition, a known method can be used as a method for adjusting the degree of opening of the warp and weft yarns, and specifically, a method in which a fiber-opening process is performed while applying and adjusting tension in the warp direction (length direction of the glass cloth) and weft direction (width direction of the glass cloth) of the glass cloth is included. In order to apply tension to the glass cloth, for example, a pinch expander, a curved rubber roller, a rotating roller, a Mirabeau roller, or a tenter may be used.

[0047] From the viewpoint of suitably satisfying the range of the ratio (Iw / If) of 1.23 or more and 1.45 or less and the basket hole area ratio of 12% or more and 20% or less in the glass cloth after the fiber-opening treatment, a method of performing the fiber-opening treatment may be mentioned in which the tension in the warp direction is adjusted to 18 to 22 N / m and the tension in the weft direction is adjusted to 5 to 10 N / m, and the water flow pressure is set to 0.9 to 1.6 MPa.

[0048] If a substance (such as a bundling agent) that inhibits the adhesion or impregnation of the resin when forming a prepreg is attached to the glass cloth before or after the fiber-spreading treatment, it is preferable to remove the substance by, for example, a heat cleaning treatment. Furthermore, it is preferable that the glass cloth that has been heat-cleaned is surface-treated with a conventionally known silane coupling agent. Such a surface treatment method may be a conventionally known method, for example, a method of impregnating the glass cloth with a silane coupling agent, a method of applying the agent, a method of spraying the agent, etc. The heat cleaning treatment and surface treatment may be performed before or after the fiber-spreading treatment.

[0049] 2. Prepreg The prepreg of the present invention is characterized by including the glass cloth of the present invention described above. Specifically, the prepreg of the present invention is characterized by including the glass cloth and a matrix resin composition impregnated into the glass cloth.

[0050] The mass ratio of the glass cloth in the prepreg of the present invention is not particularly limited. 2 By having the above-mentioned properties while having a low mass of 40% or less, it is possible to effectively suppress the occurrence of pinholes and vertical wrinkles in the prepreg even if the mass ratio of the glass cloth in the prepreg is reduced to 40% or less by mass. In view of such characteristics, a suitable example of the prepreg of the present invention is one in which the mass ratio of the glass cloth is low. Specifically, the mass of the prepreg (the total mass of the glass cloth and the matrix resin composition) (g / m 2 ) to the mass (g / m 2 The ratio of (mass of glass cloth / mass of prepreg) is preferably 10 to 40 mass%, more preferably 20 to 30 mass%, further preferably 22 to 30 mass%, and particularly preferably 22 to 25 mass%.

[0051] The matrix resin composition includes a thermosetting resin. The thermosetting resin is not particularly limited as long as it is a resin that is cured by heat, and examples thereof include phenol resin, epoxy resin, non-halogen epoxy resin, cyanate resin, maleimide resin, bismaleimide resin, modified bismaleimide resin, isocyanate resin, benzocyclobutene resin, vinyl resin, bismaleimide triazine resin, phenol resin, and thermosetting polyphenylene ether resin. The thermosetting resin may be used alone or in combination of two or more kinds.

[0052] Furthermore, the matrix resin composition may contain a curing agent and / or a curing accelerator, as required. The curing agent and / or the curing accelerator may be appropriately selected depending on the type of thermosetting resin used.

[0053] Furthermore, the matrix resin composition preferably contains an inorganic filler other than the glass cloth. Examples of the inorganic filler include silicas such as natural silica, fused silica, amorphous silica, and hollow silica; boehmite; molybdenum compounds such as molybdenum oxide and zinc molybdate; glass fillers such as alumina, talc, calcined talc, mica, glass short fibers, and spherical glass (glass fillers using E glass, T glass, UT glass (manufactured by Unitika Glass Fiber Co., Ltd.), S glass, D glass, NE glass, L glass, and LU glass (manufactured by Unitika Glass Fiber Co., Ltd.) as glass materials). These inorganic fillers may be used alone or in combination of two or more.

[0054] The average particle diameter (D50) of the inorganic filler is not particularly limited, but from the viewpoint of providing excellent properties when used for thin multilayer printed wiring board applications and further improving dispersibility, it is preferably 10 nm to 5.0 μm, more preferably 100 nm to 2.0 μm, and even more preferably 100 nm to 1.0 μm. Here, the average particle diameter (D50) means the median diameter, which is the diameter when the particle size distribution of the measured powder is divided into two and the larger side and the smaller side are equal in amount. More specifically, the average particle diameter (D50) is the value (median diameter) when the particle size distribution of the powder dispersed in methyl ethyl ketone is measured by a laser diffraction scattering type particle size distribution measuring device, and the volume accumulation from the smallest particle reaches 50% of the total volume.

[0055] From the viewpoint of improving moisture resistance, the inorganic filler is preferably surface-treated with a surface treatment agent such as a silane coupling agent. The type of the surface treatment agent is not particularly limited, but examples thereof include aminosilane coupling agents, vinylsilane coupling agents, epoxysilane coupling agents, styrylsilane coupling agents, methacrylsilane coupling agents, and silicone oligomer coupling agents. Among these, aminosilane coupling agents are preferred. The aminosilane coupling agent is a silane having one or two amino groups and one silicon atom, preferably a silane having one amino group and one silicon atom. Commercially available products of silica surface-treated with aminosilane coupling agents include "SC-2050KNK" (average particle size 0.5 μm, manufactured by Admatechs Co., Ltd.).

[0056] In the matrix resin composition, the mass ratio of the inorganic filler to the thermosetting resin is not particularly limited, but for example, the inorganic filler is preferably 10 to 400 parts by mass, more preferably 20 to 100 parts by mass, and even more preferably 20 to 50 parts by mass, per 100 parts by mass of the thermosetting resin in terms of solid content.

[0057] The prepreg of the present invention can be produced by a known method. Specifically, the method for producing the prepreg of the present invention includes a method in which the glass cloth is impregnated with a resin solution (varnish) containing a matrix resin composition, and then, if necessary, dried to volatilize volatile components, and the thermosetting resin is cured to a B-stage state (semi-cured state).

[0058] The resin solution (varnish) used in the production of the prepreg of the present invention may consist of only the matrix resin composition (non-volatile component), but may also contain a dilution solvent (volatile component). The concentration of the non-volatile component in the resin solution (varnish) is, for example, 50 to 100% by mass.

[0059] The use of the prepreg of the present invention is not particularly limited, but it is suitable as a constituent material of printed wiring boards. EXAMPLES

[0060] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the examples.

[0061] (1) Manufacturing of glass cloth and prepreg Example 1 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.3 μm, an average number of filaments of 35, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 125 / 25 mm and a weft density of 125 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. The glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and then subjected to a water flow processing at a pressure of 1.0 MPa to open the glass cloth, thereby obtaining a glass cloth roll product. The obtained glass cloth had a designed gap Iwd between adjacent warp yarns of 85 μm, a designed gap Ifd between adjacent weft yarns of 85 μm, a ratio of the measured gap Iw between adjacent warp yarns and the measured gap If between adjacent weft yarns of 1.23, and a basket hole area ratio of 19.6%.

[0062] Next, two types of varnishes for obtaining prepregs were prepared. <Composition of Varnish A> Epoxy resin (Mitsubishi Chemical Corporation jER5045B80) 100 parts by mass Hardener (Mitsubishi Chemical Corporation jER Cure DICY7) 2.7 parts by mass (dicyandiamide) Curing accelerator (2-ethyl-4-methylimidazole, manufactured by Mitsubishi Chemical Corporation) 0.2 parts by mass Dilution solvent (dimethylformamide manufactured by Kishida Chemical Co., Ltd.) 20 parts by weight Inorganic filler (Admatechs Co., Ltd. "SC-2050KNK" average particle size 0.5 μm, spherical silica surface-treated with a silane coupling agent) 25 parts by mass

[0063] <Composition of Varnish B> Modified bismaleimide resin (PRINTECH Corporation HR3070) 60 parts by weight Curing accelerator (2-ethyl-4-methylimidazole, manufactured by Mitsubishi Chemical Corporation) 0.3 parts by mass Dilution solvent (methyl ethyl ketone, manufactured by Kishida Chemical Co., Ltd.) 40 parts by weight Inorganic filler (Admatechs Co., Ltd. "SC-2050KNK" average particle size 0.5 μm, spherical silica surface-treated with a silane coupling agent) 25 parts by mass

[0064] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of varnish A to varnish B satisfied the conditions shown in Table 1, and the roll was then passed through a dryer so that the gel time, which is an index of the degree of curing of the resin, was around 110 seconds, and then wound up as is, to obtain prepreg roll product A.

[0065] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of Varnish B to the total viscosity of the prepreg roll product B satisfied the conditions shown in Table 1, and the prepreg roll product B was obtained by passing the prepreg roll product through a dryer so that the gel time was about 110 seconds and then winding the prepreg roll product B.

[0066] Example 2 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.1 μm, an average number of filaments of 34, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 135 / 25 mm and a weft density of 135 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and a fiber-opening process was performed by water flow processing at a pressure of 1.5 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 80 μm, a designed gap value Ifd between adjacent weft yarns of 80 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.29, and a basket hole area ratio of 18.4%.

[0067] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0068] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 1, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0069] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total weight of the coated roll satisfied the conditions shown in Table 1, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated roll was then passed through a dryer and wound up as is, to obtain prepreg roll product B.

[0070] Example 3 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 36, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 115 / 25 mm and a weft density of 115 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with a tenter, and a fiber-opening process was performed by water flow processing at a pressure of 1.0 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 88 μm, a designed gap value Ifd between adjacent weft yarns of 88 μm, a ratio of the actual gap value (Iw) between adjacent warp yarns and the actual gap value (If) between adjacent weft yarns of 1.34, and a basket hole area ratio of 16.4%.

[0071] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0072] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of varnish A to varnish B satisfied the conditions shown in Table 1, and the product was passed through a dryer so that the gel time was around 110 seconds and then wound up as is to obtain prepreg roll product A.

[0073] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of Varnish B to the total viscosity of the prepreg roll product B satisfied the conditions shown in Table 1, and the prepreg roll product B was obtained by passing the prepreg roll product through a dryer so that the gel time was about 110 seconds and then winding the prepreg roll product B.

[0074] Example 4 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass was woven by an air jet loom to obtain a plain weave glass cloth roll with a width of 130 cm and a warp density of 105 / 25 mm and a weft density of 105 / 25 mm. The spinning bundling agent and weaving bundling agent attached to the obtained glass cloth were then removed by heating at 400°C for 30 hours. The glass cloth was then immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. The glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and then subjected to a water flow processing at a pressure of 1.0 MPa to open the glass cloth, thereby obtaining a glass cloth roll product. The obtained glass cloth had a designed gap Iwd between adjacent warp yarns of 94 μm, a designed gap Ifd between adjacent weft yarns of 94 μm, a ratio of the measured gap Iw between adjacent warp yarns and the measured gap If between adjacent weft yarns of 1.38, and a basket hole area ratio of 14.9%.

[0075] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0076] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of varnish A to varnish B satisfied the conditions shown in Table 1, and the product was passed through a dryer so that the gel time was around 110 seconds and then wound up as is to obtain prepreg roll product A.

[0077] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of Varnish B to the total viscosity of the prepreg roll product B satisfied the conditions shown in Table 1, and the prepreg roll product B was obtained by passing the prepreg roll product through a dryer so that the gel time was about 110 seconds and then winding the prepreg roll product B.

[0078] Example 5 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 110 / 25 mm and a weft density of 110 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with a tenter, and a fiber-opening process was performed by water flow processing at a pressure of 1.2 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 83 μm, a designed gap value Ifd between adjacent weft yarns of 83 μm, a ratio of the actual gap value (Iw) between adjacent warp yarns and the actual gap value (If) between adjacent weft yarns of 1.40, and a basket hole area ratio of 12.5%.

[0079] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0080] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of varnish A to varnish B satisfied the conditions shown in Table 1, and the product was passed through a dryer so that the gel time was around 110 seconds and then wound up as is to obtain prepreg roll product A.

[0081] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of Varnish B to the total viscosity of the prepreg roll product B satisfied the conditions shown in Table 1, and the prepreg roll product B was obtained by passing the prepreg roll product through a dryer so that the gel time was about 110 seconds and then winding the prepreg roll product B.

[0082] Example 6 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 36, and a twist number of 0.5Z. The glass was woven with an air jet loom to obtain a plain weave glass cloth roll with a width of 130 cm and a warp density of 120 / 25 mm and a weft density of 122 / 25 mm. The spinning bundling agent and weaving bundling agent attached to the obtained glass cloth were then removed by heating at 400°C for 30 hours. The glass cloth was then immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with a tenter, and a fiber-opening process was performed by water flow processing at a pressure of 1.0 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 79 μm, a designed gap value Ifd between adjacent weft yarns of 75 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.44, and a basket hole area ratio of 13.8%.

[0083] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0084] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of varnish A to varnish B satisfied the conditions shown in Table 1, and the product was passed through a dryer so that the gel time was around 110 seconds and then wound up as is to obtain prepreg roll product A.

[0085] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of Varnish B to the total viscosity of the prepreg roll product B satisfied the conditions shown in Table 1, and the prepreg roll product B was obtained by passing the prepreg roll product through a dryer so that the gel time was about 110 seconds and then winding the prepreg roll product B.

[0086] Example 7 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 105 / 25 mm and a weft density of 110 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. The glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m in the weft direction (width direction) while both ends of the glass cloth were held by tenters, and a fiber-opening process was performed by water flow processing at a pressure of 1.0 MPa, to obtain a glass cloth roll product. The obtained glass cloth had a designed gap Iwd between adjacent warp yarns of 94 μm, a designed gap Ifd between adjacent weft yarns of 83 μm, a ratio of the measured gap Iw between adjacent warp yarns and the measured gap If between adjacent weft yarns of 1.44, and a basket hole area ratio of 15.0%.

[0087] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0088] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of varnish A to varnish B satisfied the conditions shown in Table 1, and the product was passed through a dryer so that the gel time was around 110 seconds and then wound up as is to obtain prepreg roll product A.

[0089] In addition, a glass cloth roll product obtained separately was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to apply Varnish B to the glass cloth. Next, the glass cloth to which Varnish B had been applied was rolled using a gap roll to reduce the mass of the prepreg (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of Varnish B to the total viscosity of the prepreg roll product B satisfied the conditions shown in Table 1, and the prepreg roll product B was obtained by passing the prepreg roll product through a dryer so that the gel time was about 110 seconds and then winding the prepreg roll product B.

[0090] Comparative Example 1 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass was woven by an air jet loom to obtain a plain weave glass cloth roll with a width of 130 cm and a warp density of 105 / 25 mm and a weft density of 105 / 25 mm. The spinning bundling agent and weaving bundling agent attached to the obtained glass cloth were then removed by heating at 400°C for 30 hours. The glass cloth was then immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 50 N / m in the warp direction (length direction) and a tension of 20 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and a fiber-opening process was performed by water flow processing at a pressure of 1.2 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 94 μm, a designed gap value Ifd between adjacent weft yarns of 94 μm, a ratio of the actual gap value (Iw) between adjacent warp yarns and the actual gap value (If) between adjacent weft yarns of 1.02, and a basket hole area ratio of 19.1%.

[0091] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0092] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0093] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total viscosity of the coated layer satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated layer was then passed through a dryer and wound up as is to obtain prepreg roll product B.

[0094] Comparative Example 2 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.1 μm, an average number of filaments of 32, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 148 / 25 mm and a weft density of 148 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) JNC Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. The glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m in the weft direction (width direction) while both ends of the glass cloth were held by tenters, and a fiber-opening process was performed by water flow processing at a pressure of 1.0 MPa, to obtain a glass cloth roll product. The obtained glass cloth had a designed gap Iwd between adjacent warp yarns of 70 μm, a designed gap Ifd between adjacent weft yarns of 70 μm, a ratio of the measured gap Iw between adjacent warp yarns and the measured gap If between adjacent weft yarns of 1.13, and a basket hole area ratio of 19.4%.

[0095] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0096] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0097] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total viscosity of the coated layer satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated layer was then passed through a dryer and wound up as is to obtain prepreg roll product B.

[0098] Comparative Example 3 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 100 / 25 mm and a weft density of 100 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 30 N / m in the warp direction (length direction) and a tension of 20 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with a tenter, and a fiber-opening process was performed by water flow processing at a pressure of 1.5 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 106 μm, a designed gap value Ifd between adjacent weft yarns of 106 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.22, and a basket hole area ratio of 18.3%.

[0099] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0100] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of varnish A to varnish B satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time, which is an index of the degree of hardening of the resin, would be around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0101] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total viscosity of the coated layer satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated layer was then passed through a dryer and wound up as is to obtain prepreg roll product B.

[0102] Comparative Example 4 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass was woven by an air jet loom to obtain a plain weave glass cloth roll with a width of 130 cm and a warp density of 125 / 25 mm and a weft density of 125 / 25 mm. The spinning bundling agent and weaving bundling agent attached to the obtained glass cloth were then removed by heating at 400°C for 30 hours. The glass cloth was then immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 20 N / m was also applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and a fiber-opening process was performed by water flow processing at a pressure of 1.0 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 56 μm, a designed gap value Ifd between adjacent weft yarns of 56 μm, a ratio of the actual gap value (Iw) between adjacent warp yarns and the actual gap value (If) between adjacent weft yarns of 1.25, and a basket hole area ratio of 9.8%.

[0103] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0104] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0105] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total viscosity of the coated layer satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated layer was then passed through a dryer and wound up as is to obtain prepreg roll product B.

[0106] Comparative Example 5 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 36, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 110 / 25 mm and a weft density of 110 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and a fiber-opening process was performed by water flow processing at a pressure of 1.0 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 98 μm, a designed gap value Ifd between adjacent weft yarns of 98 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.29, and a basket hole area ratio of 18.9%.

[0107] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0108] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0109] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total viscosity of the coated layer satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated layer was then passed through a dryer and wound up as is to obtain prepreg roll product B.

[0110] Comparative Example 6 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 38, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 105 / 25 mm and a weft density of 110 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and a fiber-opening process was performed by water flow processing at a pressure of 0.8 MPa to obtain a glass cloth roll product. The obtained glass cloth had a design gap Iwd between adjacent warp yarns of 101 μm, a design gap Ifd between adjacent weft yarns of 90 μm, a ratio of the actual gap Iw between adjacent warp yarns and the actual gap If between adjacent weft yarns of 1.33, and a basket hole area ratio of 21.7%.

[0111] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0112] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0113] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total amount of varnish B satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product B.

[0114] Comparative Example 7 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 36, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 115 / 25 mm and a weft density of 115 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with a tenter, and a fiber-opening process was performed by water flow processing at a pressure of 0.5 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 88 μm, a designed gap value Ifd between adjacent weft yarns of 88 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.34, and a basket hole area ratio of 21.5%.

[0115] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0116] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0117] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total viscosity of the coated layer satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated layer was then passed through a dryer and wound up as is to obtain prepreg roll product B.

[0118] Comparative Example 8 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass was woven by an air jet loom to obtain a plain weave glass cloth roll with a width of 130 cm and a warp density of 105 / 25 mm and a weft density of 105 / 25 mm. The spinning bundling agent and weaving bundling agent attached to the obtained glass cloth were then removed by heating at 400°C for 30 hours. The glass cloth was then immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and a fiber-opening process was performed by water flow processing at a pressure of 0.5 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 94 μm, a designed gap value Ifd between adjacent weft yarns of 94 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.35, and a basket hole area ratio of 21.5%.

[0119] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0120] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0121] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total viscosity of the coated layer satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated layer was then passed through a dryer and wound up as is to obtain prepreg roll product B.

[0122] Comparative Example 9 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 36, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 130 / 25 mm and a weft density of 130 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 50 N / m in the warp direction (length direction) and a tension of 25 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with a tenter, and a fiber-opening process was performed by water flow processing at a pressure of 1.5 MPa, to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 63 μm, a designed gap value Ifd between adjacent weft yarns of 63 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.50, and a basket hole area ratio of 8.6%.

[0123] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0124] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0125] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total amount of varnish B satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product B.

[0126] Comparative Example 10 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 36, and a twist number of 0.5Z. The glass was woven by an air jet loom to obtain a plain weave glass cloth roll with a width of 130 cm and a warp density of 125 / 25 mm and a weft density of 125 / 25 mm. The spinning bundling agent and weaving bundling agent attached to the obtained glass cloth were then removed by heating at 400°C for 30 hours. The glass cloth was then immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. The glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and then subjected to a water flow processing at a pressure of 1.0 MPa to open the glass cloth, thereby obtaining a glass cloth roll product. The obtained glass cloth had a designed gap Iwd between adjacent warp yarns of 70 μm, a designed gap Ifd between adjacent weft yarns of 70 μm, a ratio of the measured gap Iw between adjacent warp yarns and the measured gap If between adjacent weft yarns of 1.53, and a basket hole area ratio of 13.3%.

[0127] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0128] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0129] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total viscosity of the coated layer satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The coated layer was then passed through a dryer and wound up as is to obtain prepreg roll product B.

[0130] Comparative Example 11 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 110 / 25 mm and a weft density of 110 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, the glass cloth was subjected to a tension of 20 N / m in the warp direction (length direction) and a tension of 10 N / m was applied in the weft direction (width direction) while holding both ends of the glass cloth in the weft direction with tenters, and a fiber-opening process was performed by water flow processing at a pressure of 0.5 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 83 μm, a designed gap value Ifd between adjacent weft yarns of 83 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.58, and a basket hole area ratio of 16.8%.

[0131] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0132] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of varnish A to varnish B satisfied the conditions shown in Table 2, and the product was passed through a dryer so that the gel time was around 110 seconds and then wound up as is to obtain prepreg roll product A.

[0133] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of Varnish B to the total viscosity of the prepreg roll product B satisfied the conditions shown in Table 2, and the prepreg roll product B was obtained by passing the prepreg roll product through a dryer so that the gel time was about 110 seconds and then winding the prepreg roll product B.

[0134] Comparative Example 12 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 40, and a twist number of 0.5Z. The glass was woven by an air jet loom to obtain a plain weave glass cloth roll with a width of 130 cm and a warp density of 105 / 25 mm and a weft density of 105 / 25 mm. The spinning bundling agent and weaving bundling agent attached to the obtained glass cloth were then removed by heating at 400°C for 30 hours. The glass cloth was then immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, with the tension of the glass cloth set to 50 N / m in the warp direction (length direction) and no tension applied in the weft direction (width direction), the glass cloth was subjected to a fiber-opening treatment by water flow processing at a pressure of 1.0 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 94 μm, a designed gap value Ifd between adjacent weft yarns of 94 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.64, and a basket hole area ratio of 17.6%.

[0135] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0136] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0137] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total amount of varnish B satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product B.

[0138] Comparative Example 13 The glass material for the warp and weft was E-glass, with an average filament diameter of 3.6 μm, an average number of filaments of 36, and a twist number of 0.5Z. The glass material was E-glass, and the glass yarn was woven with an air jet loom to obtain a plain weave glass cloth roll with a warp density of 115 / 25 mm and a weft density of 115 / 25 mm and a width of 130 cm. Next, the spinning sizing agent and weaving sizing agent attached to the obtained glass cloth were removed by heating at 400°C for 30 hours. After that, the glass cloth was immersed in an aqueous solution containing 10 g / L of a silane coupling agent (S-350: N-vinylbenzyl-aminoethyl-γ-aminopropyltrimethoxysilane (hydrochloride) Chisso Corporation), squeezed with a padder roll, and then dried and cured at 120°C for 1 minute. Then, with the tension of the glass cloth set to 50 N / m in the warp direction (length direction) and no tension applied in the weft direction (width direction), the glass cloth was subjected to a fiber-opening treatment by water flow processing at a pressure of 0.5 MPa to obtain a glass cloth roll product. The obtained glass cloth had a designed gap value Iwd between adjacent warp yarns of 88 μm, a designed gap value Ifd between adjacent weft yarns of 88 μm, a ratio of the measured gap value (Iw) between adjacent warp yarns and the measured gap value (If) between adjacent weft yarns of 1.70, and a basket hole area ratio of 17.1%.

[0139] Next, as in Example 1, varnish A and varnish B were prepared as varnishes for obtaining prepregs.

[0140] The obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and thoroughly immersed in Varnish A to coat the glass cloth with Varnish A. Subsequently, the glass cloth coated with Varnish A was rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish A applied was adjusted so that the ratio of (a) to (b) satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product A.

[0141] Separately, the obtained glass cloth roll product was continuously unwound in the longitudinal direction (warp direction) and then thoroughly immersed in Varnish B to coat the glass cloth with Varnish B. The glass cloth coated with Varnish B was then rolled using a gap roll to obtain a prepreg mass (g / m 2 ) to the mass of glass cloth (g / m 2 The amount of varnish B applied was adjusted so that the ratio of varnish B to the total amount of varnish B satisfied the conditions shown in Table 2, and the drying conditions were adjusted so that the gel time was around 110 seconds. The product was then passed through a dryer and wound up as is, to obtain prepreg roll product B.

[0142] (2) Measurement and evaluation methods The physical properties of the glass cloth and the prepreg roll were measured and evaluated by the following methods.

[0143] 1. Average filament diameter Dw and Df (μm), average number of filaments Nw and Nf (number) The measurement was performed using a scanning electron microscope (SEM) (manufactured by JEOL Ltd., product name JSM-6390A) according to the method described above.

[0144] 2. tex This was carried out in the manner described above.

[0145] 3. Warp density Ww and weft density Wf (threads / 25mm) This was carried out in the manner described above.

[0146] 4. Measured gap between adjacent warp yarns Iw and measured gap between adjacent weft yarns If (μm) This was carried out in the manner described above.

[0147] 5. Mass of glass cloth (g / m 2 ) and thickness (μm) The mass of the glass cloth was measured and calculated according to the provisions of "7.2 Mass (mass) of cloth and mat" in the Japanese Industrial Standard JIS R 3420 2013 (General test method for glass fiber). The thickness of the glass cloth was measured and calculated according to the A method prescribed in "7.10.1 Thickness of cloth" in the Japanese Industrial Standard JIS R 3420 2013 (General test method for glass fiber).

[0148] 6. Evaluation of pinhole occurrence For each of the obtained prepreg roll products A and B, three prepregs (one set) were cut into a 400 mm x 400 mm square from three randomly selected locations aligned parallel to the width direction. A total of 50 sets of these were taken, and a total of 150 prepregs were prepared. The number of pinholes in each of the 150 prepregs was visually counted, and prepregs with four or fewer pinholes per sheet were deemed to be good products, and the good product rate (%) of the 150 sheets was calculated. Those with a good product rate of 90% or more were deemed to have passed the test.

[0149] 7. Evaluation of vertical wrinkle occurrence The number of vertical wrinkles was observed by visually inspecting a length of 1000 m at random for each of the obtained prepreg roll products A and B, and the number of vertical wrinkles per 100 m was calculated and evaluated according to the following criteria. Vertical wrinkles 10 cm or longer were counted. A: The number of vertical wrinkles was 0.0 per 100 m. B: The number of vertical wrinkles was 0.1 to 1.0 per 100 m. C: The number of vertical wrinkles was 1.1 to 5.0 per 100 m. D: The number of vertical wrinkles was more than 5.1 per 100 m.

[0150] (3) Results The physical properties of the examples and comparative examples are shown in Tables 1 and 2.

[0151] [Table 1]

[0152] [Table 2]

[0153] The glass cloths of Examples 1 to 7 have a mass of 10 g / m 2 The following conditions were satisfied: the design value Iwd of the gap between adjacent warps was 95 μm or less, the design value Ifd of the gap between adjacent wefts was 95 μm or less, the ratio (Iw / If) of the measured value of the gap between adjacent warps (Iw) and the measured value of the gap between adjacent wefts (If) was 1.23 to 1.45, and the basket hole area ratio was 12.0% to 20.0%. In the glass cloths of Examples 1 to 7, when a low-mass glass cloth was impregnated with a resin solution so that the mass ratio of the glass cloth was low to form a prepreg, the occurrence of pinholes and vertical wrinkles was significantly suppressed. In particular, in the glass cloths of Examples 3 to 7, which satisfied the basket hole area ratio of 12.0% to 18.0%, the non-defective product rate in the pinhole occurrence evaluation was 99% or more, and the occurrence of pinholes in the prepreg was significantly suppressed.

[0154] On the other hand, the glass cloths of Comparative Examples 1 and 2 had a ratio (Iw / If) of less than 1.23, and therefore the occurrence of pinholes could not be sufficiently suppressed when the low-mass glass cloth was impregnated with a resin solution and cured so that the mass ratio of the glass cloth was low.

[0155] In the glass cloth of Comparative Example 3, under the condition that the design gap value Iwd between adjacent warp yarns and the design gap value Ifd between adjacent weft yarns exceeded 95 μm, the ratio (Iw / If) was less than 1.23 and the basket hole area ratio was 12.0% to 20.0%, so that each filament was present in the glass cloth in a loose state, which caused each filament constituting the weft yarn in particular to bend, which made vertical wrinkles more likely to occur. Also, in the glass cloth of Comparative Example 3, the occurrence of pinholes in the prepreg could not be sufficiently suppressed.

[0156] The glass cloth of Comparative Example 4 satisfied the following requirements: the design gap Iwd between adjacent warp yarns is 95 μm or less, the design gap Ifd between adjacent weft yarns is 95 μm or less, and the ratio (Iw / If) is 1.23 to 1.45; however, since the basket hole area ratio was less than 12.0%, internal distortion was likely to occur in the glass cloth, and it was difficult to suppress the occurrence of vertical wrinkles when the low-mass glass cloth was impregnated with a resin solution so that the mass ratio of the glass cloth was low to form a prepreg. 2 Some even exceeded that limit.

[0157] The glass cloth of Comparative Example 5 had a design gap Iwd between adjacent warp yarns and a design gap Ifd between adjacent weft yarns that exceeded 95 μm, and was subjected to a fiber-opening process so that the ratio (Iw / If) of the actual gap between adjacent warp yarns (Iw) to the actual gap between adjacent weft yarns (If) was 1.23 to 1.45, and the basket hole area ratio was 12.0% to 20.0%. As a result, each filament was present in the glass cloth in a loose state, and as a result, each filament constituting the weft yarn in particular was bent, which made vertical wrinkles more likely to occur.

[0158] The glass cloth of Comparative Example 6 had a designed gap value Iwd between adjacent warp yarns exceeding 95 μm. Since this glass cloth was subjected to a fiber-opening treatment under relatively mild conditions, the basket hole area ratio exceeded 20.0%. Even if the ratio (Iw / If) was within the range of 1.23 to 1.45, it was difficult to suppress the occurrence of pinholes when the low-mass glass cloth was impregnated with a resin solution to reduce the mass ratio of the glass cloth to a low level to form a prepreg.

[0159] The glass cloths of Comparative Examples 7 and 8 satisfied the following requirements: the design gap value Iwd between adjacent warp yarns was 95 μm or less, the design gap value Ifd between adjacent weft yarns was 95 μm or less, and the ratio (Iw / If) was 1.23 to 1.45. However, since the basket hole area ratio exceeded 20.0%, it was difficult to prevent the occurrence of pinholes when the low-mass glass cloth was impregnated with a resin solution to reduce the mass ratio of the glass cloth to a low level to form a prepreg.

[0160] The glass cloth of Comparative Example 9 had a ratio (Iw / If) of more than 1.45 and a basket hole area ratio of less than 12.0%, and therefore the glass cloth was prone to internal distortion, and it was difficult to suppress the occurrence of vertical wrinkles when the low-mass glass cloth was impregnated with a resin solution so as to have a low mass ratio of the glass cloth to form a prepreg.

[0161] The glass cloths of Comparative Examples 10 to 13 satisfied the following requirements: the design gap Iwd between adjacent warp yarns was 95 μm or less, the design gap Ifd between adjacent weft yarns was 95 μm or less, and the basket hole area ratio was 12.0% or more and 20.0% or less. However, since the ratio (Iw / If) exceeded 1.45, the weft yarns were not sufficiently held by the warp yarns. When the low-mass glass cloth was impregnated with a resin solution and hardened so that the mass ratio of the glass cloth was low, it became difficult to prevent the weft yarns from moving slightly in the width direction of the glass cloth. As a result, the occurrence of vertical wrinkles could not be sufficiently prevented.

Claims

1. Mass is 10.0 g / m 2 The following glass cloth: The gap design value Iwd between adjacent warp yarns shown in the following formula (1) is 95 μm or less, and the gap design value Ifd between adjacent weft yarns shown in the following formula (2) is 95 μm or less, The ratio (Iw / If) of the measured gap value (Iw) between adjacent warp yarns to the measured gap value (If) between adjacent weft yarns is 1.23 or more and 1.45 or less, and A glass cloth having a basket hole area ratio represented by the following formula (3) of 12.0% or more and 20.0% or less. [0010]

2. The design gap value Iwd between adjacent warp yarns is 70 μm or more and 95 μm or less, and the design gap value Ifd between adjacent weft yarns is 70 μm or more and 95 μm or less, and 2. The glass cloth according to claim 1, wherein the basket hole area ratio of the glass cloth is 12.0% or more and 18.0% or less.

3. A prepreg comprising the glass cloth according to claim 1 or 2.

4. The prepreg according to claim 3, wherein the ratio of the mass of the glass cloth to the mass of the prepreg (mass of glass cloth / mass of prepreg) is 10 to 40 mass%.

5. Mass is 10g / m 2 The method includes a step of performing a fiber-spreading process on a glass cloth having a gap design value Iwd between adjacent warp yarns represented by the following formula (1) of 95 μm or less and a gap design value Ifd between adjacent weft yarns represented by the following formula (2) of 95 μm or less, The fiber-spreading process is performed so that a ratio (Iw / If) of an actual gap value (Iw) between adjacent warp yarns to an actual gap value (If) between adjacent weft yarns is 1.23 or more and 1.45 or less, and a basket hole area ratio represented by the following formula (3) is 12% or more and 20% or less. A method for manufacturing glass cloth. [0025]

Citation Information

Patent Citations

  • Method for producing flat glass fiber woven fabric

    JP2006063489A

  • Quartz glass cloth

    JP2009263824A

  • Glass cloth

    JP2017043873A

  • Glass cloth

    JP2018021274A

  • Glass cloth, prepreg and print circuit board

    JP2019019431A